Securitization and Democracy in Eurasia Transformation and Development in the OSCE Region - Mihr, Anja; Sorbello, Paolo; Weiffen, Brigitte (Springer Nature, 2023)
This open-access book presents cutting-edge research on securitization and democratic development in the OSCE Region. Gathering contributions by practitioners and researchers from various disciplines, it presents case studies and highlights recent activities of proactive engagement in democratic institution-building and responding to security threats from the Balkans to Central Asia. The volume is divided into three parts, the first of which focuses on security-related matters, armed conflicts, minorities, and women's safety, as well as the roles that civil society, foreign governments, social media, and external donors play in this area. These contributions illustrate how the OSCE's informal approach to peace, security, and securitization as norm entrepreneur is closely linked to the level of democracy among its member states. The second part presents a special section on the political implications of China's Belt and Road Initiative (BRI), assessing the impact of this infrastructural program on the levels of democracy and/or autocracy in Eurasia. The third part consists of short chapters outlining future research and debates. The book will appeal to students and scholars of international relations, security studies, and the human rights-politics nexus. This is the 2022 instalment in a series of books released by the OSCE Academy in Bishkek. The OSCE works to promote Minority Protection, Security, Democratic Development and Human Rights, guided by the Office for Democratic Institutions and Human Rights (ODIHR), and to enhance securitization and development policies in Eurasia, Europe, Central Asia and North America. Since being founded in 1993, the OSCE and its agencies and departments have attracted a wealth of academic research in various fields and disciplines, ranging from economic development and election monitoring to enhancing global principles of human rights and securitization.